Definitely maybe: can unconscious processes perform the same functions as conscious processes? - Hesselmann, Guido; Moors, Pieter (Frontiers in Psychology, 2015)
Hassin recently proposed the “Yes It Can” (YIC) principle to describe the division of labor between conscious and unconscious processes in human cognition. According to this principle, unconscious processes can carry out every fundamental high-level cognitive function that conscious processes can perform. In our commentary, we argue that the author presents an overly idealized review of the literature in support of the YIC principle. Furthermore, we point out that the dissimilar trends observed in social and cognitive psychology, with respect to published evidence of strong unconscious effects, can better be explained by the way how awareness is defined and measured in both research fields. Finally, we show that the experimental paradigm chosen by Hassin to rule out remaining objections against the YIC principle is unsuited to verify the new default notion that all high-level cognitive functions can unfold unconsciously.